Natural Radiation in Byproducts of the Production of Phosphoric Acid - Marcilei Aparecida Guazzelli Silveira; L. L. Cardoso; N. H. Medina (Brazilian Journal of Radiation Sciences, 2015)
Natural radiation is the largest source of radiation exposure to which man is subject. It is formed basically by cosmic radiation and the radionuclides present in the Earth crust, as 40K and the elements of the decay series of 232Th and 238U. Phosphate ores, which constitutes the raw material for the production of phosphoric acid, have a high rate of natural radiation from the decay series of 232Th and 238U. Phosphogypsum, which is naturally radioactivity, is a by-product of the production of phosphoric acid by the wet method. For each ton of phosphoric acid it is produced about 4.5 tons of phosphogypsum. This work presents the analysis of samples collected in all stages of the manufacturing process of phosphoric acid, which generates the phosphogypsum.  Gamma-ray spectrometry was used to measure the concentration of the elements of the decay series of  232Th and 238U . All analyzed samples showed a high concentration of radionuclides, promoting the need for further steps in the process in order to reduce the presence of such radionuclides in the phosphogypsum. The results indicate the radionuclide 238U has higher contribution in some samples of the intermediate stages of the process.  All samples exceeded the international average range of human exposure to terrestrial gamma radiation, which is 0.3 to 1.0 mSv/year.